2014
DOI: 10.5455/msm.2014.26.12-15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation of Hypertensive Crises in Emergency Medical Services

Abstract: Objectives: The objective of this study is to evaluate the incidence and clinical presentation of hypertensive crises in the Emergency medical services of the Community Health Centre "Dr. Mustafa Šehović" Tuzla in relation to age, sex, duration and severity of hypertension, as well as the prevalence of accompanying symptoms and clinical manifestations. Methods: The study was conducted between November 2009 and April 2010 and included 180 subjects of both sexes, aged 30-80 with a diagnosis of arterial hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 2 publications
1
23
0
7
Order By: Relevance
“…The main indings of this study was that the prevalence of hypertensive crisis among patients admitted to the medical emergency room at kassala teaching hospital was .81%, which is comparable to other study conducted by Carrillo et al, who reported a prevalence of HC of 0.6% among patients brought to the clinical emergency department in a Spanish university-af iliated hospital [11]. However it is inconsistent with the studies from Italy, Brazil, Bosnia and Pakistan where estimated prevalence of HC was reported as 3%,16%,47.2%and 56% respectively [1,[12][13][14]. The difference in the prevalence rate of HC between the later studies and our result may be justi ied by inclusion of hypertensive pseudocrisis which may mimic hypertensive urgency, which may alter the inal results of the study.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The main indings of this study was that the prevalence of hypertensive crisis among patients admitted to the medical emergency room at kassala teaching hospital was .81%, which is comparable to other study conducted by Carrillo et al, who reported a prevalence of HC of 0.6% among patients brought to the clinical emergency department in a Spanish university-af iliated hospital [11]. However it is inconsistent with the studies from Italy, Brazil, Bosnia and Pakistan where estimated prevalence of HC was reported as 3%,16%,47.2%and 56% respectively [1,[12][13][14]. The difference in the prevalence rate of HC between the later studies and our result may be justi ied by inclusion of hypertensive pseudocrisis which may mimic hypertensive urgency, which may alter the inal results of the study.…”
Section: Discussionmentioning
confidence: 44%
“…In sub-Saharan Africa the prevalence of hypertension was estimated by 30% among general population. In the Eastern Mediterranean Region, the prevalence of hypertension was reported as 26% [1,2]. The prevalence of Hypertension among non-communicable diseases has been accounted for 23.6 % and 39.6% in central and Northern Sudan respectively [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Como a elevação crítica da PA nem sempre está associada com sinais e sintomas específicos devido às características assintomáticas da doença, a maioria dos usuários foi considerada com queixas que caracterizam o não se sentir bem, sendo utilizado predominantemente o fluxograma Mal-estar em adultos. Um estudo realizado na Bósnia corroborou estes resultados quando mostrou que não se sabe em que momento da elevação persistente e significativa da PA caracteriza-se uma urgência/emergência hipertensiva, pois em aproximadamente 50% das pessoas diagnosticadas como urgência/emergência hipertensiva a doença progrediu de forma assintomática, dificultando o tratamento (13) .…”
Section: Discussionunclassified
“…Cefaleia, dor no peito e dispneia foram significativamente mais presentes em pacientes com emergência hipertensiva (p < 0,005). As manifestações clínicas da EH foram relativas à síndrome coronariana aguda (92,9%) e edema pulmonar agudo (7,1%) (13) .…”
Section: Discussionunclassified
“…AH is a relatively common condition, affecting around 22% to 41% of the adult Brazilian population [2]. In addition, it accounts for more than 7 million deaths annually [3] and is considered a risk factor for cardiovascular disease [4].…”
Section: Introductionmentioning
confidence: 99%